Democratic Governance as a Function of Ethics Management Strategies. (3rd May 2020) - Anechiarico, Frank; Segal, Lydia
Abstract : This essay makes the case for combining the study of official integrity with consideration of governance integrity based on democratic values. Our focus is on the relatively unexplored administrative mechanisms used by public and private organizations to ensure appropriate workplace conduct. We call these mechanisms, ethics management strategies (EMS). We emphasize the importance of understanding the strategies used by market and state organizations to render account within a given organization and between that organization and the larger society. Our particular focus is on the degree to which a given EMS includes voice and participation by subadministrative organizational members in the identification and enforcement of ethical standards that are used to guide behavior within the organization and between the organization and the larger society. Put differently, we are interested in the degree of ethical co-determination in governance institutions.